An intersectional approach to counseling children and adolescents with health conditions - Park-Taylor, Jennie; Keitel, Merle A. (Intersectional approach to counseling and health., 2024)
"The purpose of the present book, An Intersectional Approach to Counseling Children and Adolescents with Health Conditions, is to provide mental health professionals and students of counseling, medicine, psychology, social work, and other helping professions, with useful information and helpful suggestions for their work with children and adolescents who experience significant health issues. The chapter authors rely on an intersectional understanding of the human experience and specifically focus on how diverse youth experience, understand, and seek support for specific health conditions and illnesses. Considering contemporary research that has shed light on some of the ways individuals' multiple social identities interconnect and interact to compound experiences of illness, health psychology researchers would benefit from applying an intersectional lens in their explorations of the micro and macro-level variables that influence pathways towards health and illness for different groups (Heard et al., 2020). For mental health practitioners, an intersectional perspective on diverse children and adolescents' experiences of specific health conditions will more likely lead to innovative and inclusive interventions that target change at multiple levels (Heard et al., 2020). We are confident that our book will be of great use to mental health practitioners and students who plan to or are currently working with children and adolescents with significant health issues. Readers of the book can focus on a specific health condition that is common among children/adolescents and develop their knowledge, skills, and awareness of the cultural and systemic considerations in working with children/adolescents and their families. Particular attention can be paid to the ways in which the clients' and the counselors' intersectional social identities may influence counseling children and adolescents with significant health issues"--